Guided self-help cognitive behavioural therapy for depression in primary care: a randomised controlled trial. - Christopher Williams (Public Library of Science (PLoS), 2013)
Background Access to Cognitive behavioural therapy (CBT) for depression is limited. One solution is CBT self-help books. Trial Objectives: To assess the impact of a guided self-help CBT book (GSH-CBT) on mood, compared to treatment as usual (TAU). Hypotheses GSH-CBT will have improved mood and knowledge of the causes and treatment of depression compared to the control receiving TAUGuided self-help will be acceptable to patients and staff. Methods and findings Participants Adults attending seven general practices in Glasgow, UK with a BDI-II score of ≥14. 141 randomised to GSH-CBT and 140 to TAU. Interventions RCT comparing 'Overcoming Depression: A Five Areas Approach' book plus 3-4 short face to face support appointments totalling up to 2 hours of guided support, compared with general practitioner TAU. Primary outcome The BDI (II) score at 4 months. Numbers analysed: 281 at baseline, 203 at 4 months (primary outcome), 117 at 12 months. Outcome Mean BDI-II scores were lower in the GSH-CBT group at 4 months by 5.3 points (2.6 to 7.9, p<0.001). At 4 and 12 months there were also significantly higher proportions of participants achieving a 50% reduction in BDI-II in the GSH-CBT arm. The mean support was 2 sessions with 42.7 minutes for session 1, 41.4 minutes for session 2 and 40.2 minutes of support for session 3. Adverse effects/Harms: Significantly less deterioration in mood in GSH-CBT (2.0% compared to 9.8% in the TAU group for BDI-II category change). Limitations Weaknesses: Our follow-up rate of 72.2% at 4 months is better than predicted but is poorer at 12 months (41.6%). In the GSH-CBT arm, around 50% of people attended 2 or fewer sessions. 22% failed to take up treatment. Conclusions GSH-CBT is substantially more effective than TAU. Trial registration Controlled-Trials.com ISRCTN13475030.